Vigilância genômica de SARS-CoV-2 no estado do Rio Grande do Sul, Brasil - Castro, Thaís Regina y (2024)
In January 2020, a new species of coronavirus was described, SARS-CoV-2, attributed to cases of pneumonia reported in Wuhan, China, at the end of 2019. The pathogen spread, leading to the World Health Organization Health (WHO) declaring a pandemic in March, 2020. After the first wave, caused by the wild-type of the virus, the emergence of variants was observed, highlighting the variants of concern (VOCs) Alpha, Beta, Gamma, Delta and Omicron. One of the main obstacles that Brazil faced during the pandemic can be attributed to the continental dimensions of its territory. In Rio Grande do Sul (RS), testing measures were implemented to identify cases of SARS-CoV-2 infection and strategies for carrying out genomic surveillance of the virus. Genomic surveillance can provide insights into pathogens, their evolution and circulation. The objective of this work was to carry out genomic surveillance of SARS-CoV-2 variants in RS. To achieve this, positive samples were sequenced locally, from June 2021 to October 2023 and compiled with genetic sequences available on GISAID. Bioinformatic analysis was performed to genome assembly, identify lineages, polymorphism, spatio-temporal and phylogenetic analysis. The number of cases and deaths from COVID-19, sample collection date, sex, age, location and vaccination status data were obtained from government databases. In total, 1455 samples were sequenced and 4775 genomes were obtained from GISAID. In June 2021, after a period of the Gamma variant predominance, the introduction of the Delta variant was identified in RS, in a tourist region. In October, the variant already accounted for more than 70% of infections. The number of confirmed cases and deaths remained stable during the Delta introduction period and it is estimated that 40% of the population had already received at least one dose of the vaccine. By examining the genetic sequences of the variant, 45 mutations were identified, including three additional ones, I1091V and T4087I (ORF1a), and A23V (ORF3a). The substitution rate was estimated at 5.43x10−4 substitutions/site/year. The Omicron variant was identified in the state in October 2021 and became predominant in the first week of 2022. There was a 46-fold increase in the number of cases and 9.2-fold in deaths. Proportionally to the number of cases, the Delta variant had a higher lethality (2.7%) than the Ômicron (0.3%). During this period, it is estimated that 67% of the RS population received one dose of the vaccine. In total, the circulation of 163 Omicron lineages were detected in the state. Among individuals infected with this variant, 35.6% were vaccinated with at least three doses, while those who were not vaccinated comprised 3.9% of the total. Most cases of SARS-CoV-2 infection occurred in females and individuals over the age of 43. The results obtained reinforce the complex interaction between viral evolution, demographic factors, vaccination strategies and the dynamics of virus transmission, highlighting the importance of ongoing genomic surveillance, vaccination efforts, and public health measures for effective control of COVID19.